Failure analysis of an offshore drilling casing under harsh working conditions. (February 2021) - Shi, Lei; Luo, Kai; Wang, Jiangang; Feng, Ding; Zhang, Hong; Cao, Xinjian
Highlights: We conducted a failure analysis of an N80 casing fracture in a certain well. Large oxide-based metallurgical inclusions in the casing decreased its strength. Suggestions are made to avoid such accidents in the future. Abstract: An N80 casing in a certain oil well was broken. After the casing was pulled out, many cracks, sand holes, and corrosion and rust marks were observed in the casing fracture. To test the cause of the fracture, failure simulation using ANSYS software was carried out. Metallographic analysis test, chemical composition analysis test, and conventional mechanical performance test of the casing body were designed, and finally the failure analysis of the casing fracture was completed. The results revealed several large-scale oxide metallurgical inclusions in the casing near the upper end of the wellhead, which reduced the strength of the casing material and caused the casing to crack at the maximum stress position. In addition to harsh service environment, the casing was subjected to strong stress, which exceeded the strength limit of the casing and eventually caused the casing to break. The casing material met the standard requirements at all parts except the fracture areas. A calculation method is proposed for the ocean current and wind force; the method has high accuracy and can be used for analyzing similar offshore conditions. To prevent accidents, it is recommended to strictly control the heat treatment process of the casing material, optimize its microstructure, test its performance before deployment, and establish a real-time analysis system. Timely adjustments should be made to the operating schedule when operating in harsh environments.